PENGARUH KARAKTERISTIK INTERNAL PERUSAHAAN DENGAN STIMULAN KEBIJAKAN PEMERINTAH TERHADAP PENGGUNAAN INFORMASI AKUNTANSI PADA PERUSAHAAN KECIL DI KOTA MATARAM - Ni Nyoman Yuliati (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2015)
This study aims to examine the influence of internal factors (such as, owners’ commitment,training, employees’ competence and teamwork) and government policies, functioning as themoderate variable, on the utilization of accounting information.This study employed a quantitative approach, in which the subject of the research study wasfocused on small manufacturing businesses. Initially the researcher wanted to use all of the subjectsto be the respondents of the study. However, out of the total 48 small business people contacted,only 42 people completed and returned the questionnaires. The collected data was then analyzedusing Moderating Regression Analysis (RMA).The resulting model and the test of significance found that the internal factors significantlyinfluencing the use of accounting information in small businesses were owners’, their levels ofeducation, training, and employees’ competence. The external factors, i.e. government policies,which served as a moderate variable in this study, were negligible because these factors proved tobecome insignificant stimulants that influenced the internal factors in the utilization of accountinginformation.